Core Size Conversion: Route for Exclusive Synthesis of Au38 or Au40 Nanomolecules - Nimmala, Praneeth Reddy; Jupally, Vijay Reddy; Dass, Amala (Langmuir, 2014)
Gold nanomolecules with a precise number of gold atoms and ligands have promise for catalytic, optical, and biomedical applications. For practical applications, it is essential to develop synthetic protocols to prepare monodisperse gold nanomolecules. A typical synthesis yields a number of nanomolecules with discrete numbers of core atoms. Thermochemical treatment in the presence of excess thiol, etching, is known to narrow down the number of discrete nanomolecules, by selective degradation of sizes with lower stability. Au38(SR)24 and Au40(SR)24 are abundantly formed in these etching reactions due to their extraordinary stability to chemical etching. These nanomolecules are of high interest due in part to its stability, X-ray crystallographic structure availability (Au38), and intrinsic chirality arising from the arrangement of the Au-SR interface. However, the synthetic routes typically yield a mixture of Au38 and Au40, demanding extensive separation protocols. Here, we present a synthetic route to prepare either Au38 or Au40 exclusively in the product of etching. This was made possible by conducting a comprehensive mechanistic study starting from single-sized reactant. Au67 on etching yields Au40 exclusively. Au103–105(SR)45–46 on etching also yields Au40 exclusively. Clusters of various sizes smaller than Au67 on etching yield Au38 exclusively. This is the first direct evidence for the exclusive formation of Au38 and Au40 nanomolecules by core size conversion. Mass spectrometry was used to study the core size conversion reactions to understand the mechanism. Au38 and Au40 nanomolecules form via different intermediates, as observed in the mass spectrometry data.